KAJIAN TEOREMA TITIK TETAP DI RUANG B-METRIK YANG DIPERPANJANG - Umam, Ahmad Khairul; Alfan, Aris; Isro'il, Ahmad; Shahadah, Zaqiyatus; Muamalah, Amanda Fatma (Universitas Negeri Surabaya, 2024)
This research gives more explaination in proof of theorem. The theorem is about existence and uniqueness a point is called fixed point in an extended b-metric space. Beside that, also we give example about extended b-metric space.